Guide to Wireless Network Security - Vacca, John R. (Springer US : Imprint: Springer, 2006)
The steady growth of WiFi in the enterprise demands that corporate IT teams learn and adopt new security methodologies tailored to the unique requirements and weaknesses of wireless networks. Network and security staff must first evaluate a potentially confusing set of authentication and encryption mechanisms to be used in the network. Depending on the security selected, IT will then need to establish and document the enterprise WLAN security policy, including mechanisms to validate user compliance and monitor for inherent network vulnerabilities. With a defined policy in place, IT staff can turn their attentions to protecting the network from snooping and an ever-expanding list of wireless attacks. The Guide to Wireless Network Security addresses each of these areas in detail and identifies the real-world best practices needed to deploy and maintain a secure wireless network. Guide to Wireless Network Security is an authoritative, clearly presented guide to key foundation topics and technology frameworks for designing and maintaining secure, reliable operations. From basic concepts to designing principles to deployment, all critical concepts and phases are clearly explained and presented. This guide includes coverage of wireless security testing techniques and prevention techniques for intrusion (attacks). Guide to Wireless Network Security is designed for a professional audience composed of researchers and practitioners in industry and wireless networks administrators. This book is also suitable for graduate-level students in computer science and electrical engineering.